2014
DOI: 10.1097/bot.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Reduction and Percutaneous Fixation of Selected Calcaneus Fractures

Abstract: Level IV Therapeutic. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…The reported subsidence might be due to suboptimal screw placement and fixation technique, poor patient compliance, and/or a too aggressive rehabilitation protocol. Our patients were permitted full weightbearing 8 weeks after surgery, while Woon et al, 33 Sivakumar et al, 26 and Law et al 18 permitted full weightbearing after 12 weeks. This might contribute to the amount of subsidence of the Böhler angle observed in the present study.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The reported subsidence might be due to suboptimal screw placement and fixation technique, poor patient compliance, and/or a too aggressive rehabilitation protocol. Our patients were permitted full weightbearing 8 weeks after surgery, while Woon et al, 33 Sivakumar et al, 26 and Law et al 18 permitted full weightbearing after 12 weeks. This might contribute to the amount of subsidence of the Böhler angle observed in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…Law et al 18 observed a subsidence from 18.7 degrees postoperatively to 17.6 degrees at long-time follow-up. In their study, Sivakumar et al 26 had a subsidence from 25.0 degrees postoperatively to 23.4 degrees at final follow-up. However, Tantavisut et al 27 reported a postoperative Böhler angle of 18.1 degrees subsiding to 13.1 degrees at 3 months postoperatively after using a percutaneous technique on 182 feet in 153 patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As the study by Sivakumar and colleagues 15 demonstrates, minimally-invasive fixation of calcaneal fractures significantly reduces the risk of soft-tissue complications and is particularly feasible in patients with less severe fracture patterns (Sanders Type II). As the study by Sivakumar and colleagues 15 demonstrates, minimally-invasive fixation of calcaneal fractures significantly reduces the risk of soft-tissue complications and is particularly feasible in patients with less severe fracture patterns (Sanders Type II).…”
mentioning
confidence: 99%
“…As the study by Sivakumar and colleagues 15 demonstrates, minimally-invasive fixation of calcaneal fractures significantly reduces the risk of soft-tissue complications and is particularly feasible in patients with less severe fracture patterns (Sanders Type II). 15 The authors do not discuss earlier studies using arthroscopically-assisted percutaneous reduction and screw fixation for DIACF's, but the results from these studies involving 13 to 24 patients followed for 1 to 10 years showed that excellent results can also be obtained in the medium term. Consequently, the authors' short-term results with zero infections and good to excellent outcome scores in 9 patients at 14 months follow-up compare favourably with other reported percutaneous reduction techniques, most of them involving traction.…”
mentioning
confidence: 99%